THE SEGMENTAL INFORMATION DISCLOSURES IN ACCORDANCE WITH THE REQUIREMENTS OF IFRS 8 - Salahaddin Azzat, Rezan (Journal of process management and new technologies, 2018)
AbstractThis research purposes at identifying the level of segmental information disclosure in the annual financial reports of the banks operating in Iraq for the period 2016, through the use of indicators prepared in accordance with the requirements of IFRS 8. The significance of the research stems from the reputation of objective information provided by the segmental financial reports that contribute to the addition of a new type of accounting information on the performance of the bank's segments to meet the needs of the financial reports users. However, in accordance with the research findings, this research presented a set of recommendations, the most important is the necessity of the banks operating in Iraq to comply with all the requirements of the segmental information disclosure that are in line with the requirements of IFRS 8.
Keywords: INFORMATION; BANKS